Improving soil fertility and crop yield in a tropical region with palisadegrass cover crops - Crusciol, Carlos A. C. [UNESP]; Nascente, Adriano S.; Borghi, Emerson; Soratto, Rogério P. [UNESP]; Martins, Priscila O. [UNESP] (Wiley, 2015)
In tropical regions with dry winters, low plant biomass accumulation during the period between spring–summer crop cultivations can negatively impact soil resources and make the no-till (NT) system unsustainable. Incorporating palisadegrass [Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster] [syn. Brachiaria brizantha (Hochst. Ex A. Rich) Stapf] in traditional grain production areas could improve soil quality for subsequent crops and lead to positive effects on grain yield. The objective of this study was to evaluate the effects of growing palisadegrass on soil fertility, plant nutrition, and grain yield of subsequent cash crops in a tropical region. The experiment was performed in southeastern Brazil in plots that were grown for two consecutive growing seasons (2002–2003 and 2003–2004) with either monocropped corn (Zea mays L.) or corn intercropped with palisadegrass. An initial evaluation of soil fertility was performed in November 2004 when the land was either fallow (following monocropped corn) or covered by palisadegrass (intercropped areas). After the preceding treatments, the following crops were cultivated: soybean [Glycine max (L.) Merr.] during the 2004– 2005 and 2005–2006 spring–summer, white oat (Avena sativa L.) during the 2005 and 2006 fall–winter, and corn during the 2006–2007 spring–summer. Intercropping palisadegrass with corn increased the soil fertility compared to monocropped corn. Soybean, white oat, and corn all had higher leaf macronutrient concentrations and grain yields in previously intercropped areas than in monocropped areas. Therefore, the periodic, short-term incorporation of a perennial forage grass, such as palisadegrass, as a cover crop is recommended to increase grain production and to improve the soil fertility of grain-production areas.